Link between Tangible Investment Rate and Labour Productivity in the European Manufacturing Industry - Stundziene, Alina; Baliute, Asta (Panoeconomicus, 2022)
This paper analyses the link between the tangible investment rate and apparent labour productivity in the European manufacturing industry. The research results show a negative and opposite relation between apparent labour productivity and investment rate, that is, changes in apparent labour productivity cause changes in investment in tangible assets but not vice versa. The findings do not show any significant differences among European countries when the relation between apparent labour productivity and investment rate is analysed. However, when analysing the gross investment in tangible goods, as well as in machinery and equipment, period effects are observed. A crisis and economic slowdown reduce investment in tangible capital. Meanwhile, the growth of the economy spurs more investment. The negative correlation between apparent labour productivity and investment rate indicates that investment in tangible assets is ineffective. An analysis on individual countries is required in order to reach more nuanced conclusions. Keywords: Labour productivity, Investment rate, Tangible investment, Manufacturing industry. JEL: D24, D92, J24, L60.